400=y*(30+y)

Simple and best practice solution for 400=y*(30+y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 400=y*(30+y) equation:


Simplifying
400 = y(30 + y)
400 = (30 * y + y * y)
400 = (30y + y2)

Solving
400 = 30y + y2

Solving for variable 'y'.

Reorder the terms:
400 + -30y + -1y2 = 30y + -30y + y2 + -1y2

Combine like terms: 30y + -30y = 0
400 + -30y + -1y2 = 0 + y2 + -1y2
400 + -30y + -1y2 = y2 + -1y2

Combine like terms: y2 + -1y2 = 0
400 + -30y + -1y2 = 0

Factor a trinomial.
(10 + -1y)(40 + y) = 0

Subproblem 1

Set the factor '(10 + -1y)' equal to zero and attempt to solve: Simplifying 10 + -1y = 0 Solving 10 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1y = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1y = 0 + -10 -1y = 0 + -10 Combine like terms: 0 + -10 = -10 -1y = -10 Divide each side by '-1'. y = 10 Simplifying y = 10

Subproblem 2

Set the factor '(40 + y)' equal to zero and attempt to solve: Simplifying 40 + y = 0 Solving 40 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + y = 0 + -40 Combine like terms: 40 + -40 = 0 0 + y = 0 + -40 y = 0 + -40 Combine like terms: 0 + -40 = -40 y = -40 Simplifying y = -40

Solution

y = {10, -40}

See similar equations:

| 7(10+7x)=7(4x+3) | | xy+3y=8x-20 | | 2x=10-3y | | 8v^2+16v-64=0 | | 23x+12=21x+34 | | (-0.4-2)+1.3= | | x/6=7.68 | | 6u+8v-7(6u-4v+8w)= | | 6x=5x+2(x-1)-x+3 | | 3.14*4*2.25/3= | | 310/2.0=333/X | | 3.14*4= | | -5(2x-3)= | | 3(5x+4)=9 | | xy+3y=8y-20 | | x^3-17x^2+90x-140=0 | | 4a-3a=20 | | 7f-15=f+3 | | -16x^2+8t+8=0 | | 15x+19y=4 | | 7(q-4)+3(q-5)=-23 | | 3x*x+5-2x-1= | | 19x+15y=3 | | y+9=5(x+10) | | 3xsquared+5-2x-1= | | n-26=(-13) | | 8(3x-3y)-4(8x+3y)= | | 6e+7=2e+11 | | y=1.05e+15 | | 9x+9=6-(8x-4) | | 39x=64x+24 | | 10x+12+4x-3= |

Equations solver categories